Engineered Recombinant Protein Production Systems Originated from Escherichia coli - Ranjbari, Javad (Trends in Peptide and Protein Sciences, 2019)
Selection of a suitable host strain is an important step in recombinant production of heterologous proteins. As the prokaryotic systems and especially Escherichia coli (E. coli) cells are the most attractive host in therapeutic protein production, various derivatives of this organism have been developed to overcome the limitations exist in recombinant protein production, such as inefficient expression and folding of target proteins with eukaryotic origin. This review summarized key strategies for E. coli engineering and introduced some new and applicable engineered E. coli strains that produce more complex proteins for therapeutic and research use in the future. HIGHLIGHTS • Selection of a suitable host is an important step in recombinant protein production. • Escherichia coli cells are the most attractive host in therapeutic protein production. • Engineered strains had developed to produce active protein with suitable conformation in industrial scale. • Classical mutagenesis & genome engineering are two important strain engineering strategies.